The War for Lebanon, 1970-1983 - Rabinovich, Itamar (Cornell University Press, 2019)
In this timely and significant book, an eminent scholar recounts the history of modern and contemporary Lebanon-a history marked by continuing strife and tragedy. A judicious account of Lebanon's sustained domestic conflict, this book analyzes the exacerbating effects that foreign intervention and occupation have had on the Lebanese political order. Itamar Rabinovich opens with a chapter explaining the paradoxical nature of the Lebanese state. He follows the events of a particularly important twelve-year period through four distinct stages: the collapse of the Lebanese political system between 1970 and 1975; the civil war of 1975-1976; the lingering crisis of the years 1976-1982; and the war of 1982. Bringing the story up to date, he devotes a chapter and a postscript to events since September 1982. Grounding his interpretation and narrative firmly in a historical perspective, Rabinovich provides an unbiased treatment of the perceptions and intentions of the participants-a rarity in books on this subject. He sorts out the rich mix of domestic, regional, and international political figures and uses a variety of Arab and Israeli sources to clarify military moves, political ties, and diplomatic initiatives. The author offers a thorough review of the internecine rivalries between different religious groups, political factions, economic interests, and the international allies and opponents with longstanding stakes in Lebanon. His explanation of the delicate balancing and counterbalancing required of any Lebanese regime trying to establish order between these antagonistic elements helps to clarify the basic causes of the current crisis. Writing from a solid background in modern Middle Eastern studies, Rabinovich successfully delineates the interplay between Lebanon's domestic unrest and the major problems that continue to plague the Middle East.